Structural relationship between subsurface oil fields in the North Dezful Embayment: Qaleh Nar, Lower and Upper Balarud Anticlines (central Zagros, Iran) - Ahmad Radmehr; Soumyajit Mukherjee; Mohammad Seraj; Raana Razavi Pash (Bulletin of the Mineral Research and Exploration)
How subsurface anticlines (oil fields) link structurally with faults is of great relevance in the exploration and development of oil fields. In this context, we investigate the geometric relation between lower Balarud (LBR), upper Balarud (UBR) and Qaleh Nar (QN) subsurface anticlines that are the main oil fields in the Northern Dezful Embayment, central Zagros. The Asmari (As) and the Bangestan (Bng) reservoirs are studied geophysically using seismic profiles, well data and underground contour maps (UGC). Interpretation of 3500 m deep seismic profiles indicates the geometry of the studied subsurface anticlines differs vertically and horizontally to a significant proportion. The interpreted structures much resemble As and Bng horizons in each anticline. The UBR got overturned on the LBR due to thrusting possibly in the Late Miocene. The LBR, like a rabbit-ear structure, is situated at the northern edge of the QN. The lower and upper Chenareh and LBR and UBR resemble structurally and are separated mutually by a steep (strike-slip) fault. The fault separates the LBR and UBR from the QN. Interaction of different factors: change in overburden pressure, rate of deformation and uplift in the different parts of the subsurface anticlines moved and accumulated Gachsaran Formationtowards both limbs of the anticlines.